THE PERCEPTION OF THE TRADITIONAL DEATH CEREMONY (RAMBU SOLO) ON TOP OF FINANCIAL MANAGEMENT FOR TORAJA MIGRANTS IN SANGATTA AND TANGERANG USING AN ETHNOGRAPHIC APPROACH - Ayu Wulandari; Annisa Liestiani; Budiyanto Hariandja; Jerry Heikal (Jurnal Media Akademik (JMA), 2024)
The Rambu Solo is a traditional death ceremony carried out by the Toraja people to honor the spirits of the deceased. In reality, the implementation of the Rambu Solo Culture has a phenomenon where the economic is low, the Rambu Solo ceremony cost is very expensive, but it is still being held by Toraja people. The method used in this research is qualitative with an ethnographic approach. This research aims to learn from the Toraja people who have migrated and settled in Sangatta and Tangerang, why the Rambu Solo ceremony is still being held even though the implementation costs are very expensive, how their perception of the Rambu Solo customs, and how they manage their finances for the implementation of this traditional death ceremony by analyzing the behaviour of a group of Toraja people in Sangatta and Tangerang who already have families and are domiciled in the Sangatta and Tangerang areas. Based on the results of the interview, it is concluded that overall, the perception of Toraja migrants towards the Rambu Solo ceremony on top financial management is the Rambu Solo has important values so this ceremony must be preserved even though the costs incurred are very expensive. These share values are preserving of tradition and cultural heritage; the importance of spirituality, belief and perceptions of death and the afterlife (Aluk To Dolo); solidarity (mutual cooperation, caring, helping and share each other, consolidation of family and social network) (Misa' Kada Dipotuo, Pantan Kada Dipomate); respect for the ancestors; and recognition of social status, power (prestige) and social sanction (tula).